Copper based superhydrophobic microchannels: fabrication and its effect on friction reduction. (April 2015) - Tang, Y.; Fu, T.; Liu, Q.; Luo, W.
<x content-type="archive" xml:space="preserve">Abstract</x> Copper based superhydrophobic surfaces are fabricated using a laser electrodeposited composite method, which is able to form a dual rough microstructure. It is found that the static contact angles on these special microstructure surfaces are bigger than 150° and rolling angles are smaller than 5° when there is no low energy material coating on surfaces. It is also found that the pressure drops on microchannel surfaces composed with these microstructures show an increasing trend with the widening of channel. Under the condition of laminar flow, they are obviously smaller on superhydrophobic microchannels than on a smooth channel. Owing to the superhydrophobic structures, the friction factor reduces compared with a smooth surface. The biggest reduction value is 48·8%, and the smallest is 46·9%.